Perception, as you make it. (2016) - Vinson, David W.; Abney, Drew H.; Amso, Dima; Chemero, Anthony; Cutting, James E.; Dale, Rick; Freeman, Jonathan B.; Feldman, Laurie B.; Friston, Karl J.; Gallagher, Shaun; Jordan, J. Scott; Mudrik, Liad; et al.
Abstract: The main question that Firestone & Scholl (F&S) pose is whether "what and how we see is functionally independent from what and how we think, know, desire, act, and so forth" (sect. 2, para. 1). We synthesize a collection of concerns from an interdisciplinary set of coauthors regarding F&S's assumptions and appeals to intuition, resulting in their treatment of visual perception as context-free.